2013
DOI: 10.1080/08870446.2013.822078
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating satisfaction with physical activity: An examination of the day-to-day associations between experiences with physical activity and satisfaction during physical activity initiation

Abstract: Satisfaction with physical activity is known to be an important factor in physical activity maintenance, but the factors that influence satisfaction are not well understood. The purpose of this study was to elucidate how ongoing experiences with recently initiated physical activity are associated with satisfaction. Participants (n = 116) included insufficiently active volunteers who initiated a self-directed physical activity regimen and completed daily diaries about their experiences for 28 days. We used mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 37 publications
6
42
0
Order By: Relevance
“…These subconscious associations could in turn be the underlying reason for explicit, affective attitudes ( Bluemke et al, 2010 ). To review alternative effect mechanisms, it is necessary to include further motivational constructs in future examinations [e.g., self-efficacy ( Kwan and Bryan, 2010 ; Schneider and Kwan, 2013 ); affective outcome expectancies and satisfaction ( Baldwin et al, 2013 ; Loehr et al, 2014 )]. In doing so, one could further elaborate on the potential of affective predictors of the adoption and maintenance of physical exercises in comparison to other motivational and volitional predictors of behavior, which were already established in other studies [e.g., outcome expectancies, self-efficacy, intention ( Gellert et al, 2012 ); intention ( Mohiyeddini et al, 2009 ); outcome expectancies, fulfillment of outcome expectancies, action self-efficacy, ( Klusmann et al, 2016 )].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These subconscious associations could in turn be the underlying reason for explicit, affective attitudes ( Bluemke et al, 2010 ). To review alternative effect mechanisms, it is necessary to include further motivational constructs in future examinations [e.g., self-efficacy ( Kwan and Bryan, 2010 ; Schneider and Kwan, 2013 ); affective outcome expectancies and satisfaction ( Baldwin et al, 2013 ; Loehr et al, 2014 )]. In doing so, one could further elaborate on the potential of affective predictors of the adoption and maintenance of physical exercises in comparison to other motivational and volitional predictors of behavior, which were already established in other studies [e.g., outcome expectancies, self-efficacy, intention ( Gellert et al, 2012 ); intention ( Mohiyeddini et al, 2009 ); outcome expectancies, fulfillment of outcome expectancies, action self-efficacy, ( Klusmann et al, 2016 )].…”
Section: Discussionmentioning
confidence: 99%
“…Psychological and physical experiences appear to be especially relevant for the longer-term maintenance of exercise behavior ( Rothman, 2000 ). There is some initial empirical support that positive exercise experiences influence subsequent affective outcome expectancies ( Loehr et al, 2014 ) or satisfaction with the exercise behavior ( Fleig et al, 2011 ; Baldwin et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the past 10–20 years there has been greater attention to affective processes among PA promotion researchers (Ekkekakis, 2003; Ekkekakis et al, 2005; Kiviniemi et al, 2007; Rhodes et al, 2007, 2009; Williams et al, 2008, 2012; Schneider et al, 2009; Kwan and Bryan, 2010a,b; Conner et al, 2011; Rose and Parfitt, 2012; Baldwin et al, 2013). Much of this research has focused on the way people feel in response to intentional exercise—a form of PA performed for the purposes of health and fitness.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that satisfaction can be increased both by the awareness in a specific positive situation and by the reduction of negative thoughts, e.g. about physical activity (16); something which may be facilitated by practising mindfulness (17). All people have a varying intrinsic, albeit modifiable, trait to be aware of the present moment; dispositional mindfulness (18).…”
Section: Introductionmentioning
confidence: 99%